Dynamic behaviour of rotating functionally graded Timoshenko beam via B-spline collocation method - Chichkhede S.; Mahapatra D.; Sanyal S.; Bhowmick S. (Applied and Computational Mechanics, 2025)
The dynamic behaviour of a rotating Timoshenko functionally graded (FG) beam is investigated, with material properties varying along the height of the beam according to a power-law distribution. The study investigates how key parameters such as the power-law index, rotational speed, slenderness ratio, and various functionally graded material (FGM) compositions affect the dynamic response of the beam. The governing equations, which incorporate shear deformation and rotary inertia effects, are formulated and solved using the B-spline collocation method. The results provide critical insights into how these parameters affect the natural properties of FG beams, contributing to optimization and development for the design of advanced rotating structures in engineering applications.